Campaigning against conflict - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2008)
Frustrated by the lack of mainstream media attention, international human rights organizations are using the internet to maintain focus on the conflict in Darfur.